Comprehensive Overview of Nurses' Knowledge and Skills in Documenting Nursing Care Accurately and Efficiently at Community Health Centres - Suwarto, Tri; Kartikasari, Fitriana; Purnomo, Jeki (JENDELA NURSING JOURNAL, 2025)
Proper documentation functions as an accurate medical record, legal proof, communication tool among healthcare professionals and a foundation for evaluating and improving services, making nurses' ability to document nursing care accurately and also efficiently vital for research and development. This research aims to provide a comprehensive overview of the knowledge, skill levels of nurses in community health centres in documenting nursing care accurately and efficiently. This quantitative descriptive research use a total sampling approach on all nurses working in community health centres in one district in Indonesia. A questionnaire instrument is used to assess nurses' Knowledge while the skill observation is conducted by using a checklist to assess nurses' practical skills in performing nursing care documentation, including completeness, timeliness, use of standard terms, neatness of documentation. Data is analysed to examine the distribution of knowledge, skill levels possessed by the nurses. Results indicate nurses possess high levels of theoretical knowledge. However, practical skills often lag behind, with several skill areas requiring reinforcement. In assessment, significant gaps exist in biopsychosocial-spiritual data collection skills compared to nurses' knowledge. In diagnosis, data analysis and interpretation skills need improvement despite adequate nursing knowledge. In planning, nurses demonstrate difficulties in formulating action plans based on specific objectives. Nursing intervention implementation, such as health education for families and self-hygiene training, also shows disparities between knowledge and skills. Evaluation of patient and family capabilities shows balanced results. However, nursing care documentation still requires improvement in recording skills. Proposed recommendations include developing continuous training programmes, fostering interdisciplinary collaboration, enhancing family education, improving documentation skills, conducting regular evaluations of nurses' knowledge and skills.